Reduction of single DC bus capacitance in photovoltaic cascaded multilevel converter - Turki Kahawish Hassan (Institute of Advanced Engineering and Science, 2020)
This paper presented single DC bus single phase seven level cascaded H-bridge (CHB) inverter for multi-panel photovoltaic grid-connected applications. A single DC bus supplying flyback converters to produce DC link voltages for CHB cells is suggested. A balanced operation of CHB inverter cells is obtained irrespective to power unbalance occurred by individual maximum power point tracking boost converter of photovoltaic (PV) panels due to the non-uniform irradiation and partial shading. A DC bus voltage control system with addition of estimated DC bus ripple voltage to the reference is proposed to eliminate the second order harmonic contained in the feedback voltage of DC bus enabling to design high bandwidth of DC voltage control loop. This produces fast dynamic response, low total harmonic distortion (THD) of grid current and smaller DC bus capacitance. Mathematical modeling of bus voltage control system is presented. PSIM simulation program is used and the simulation results are obtained to validate the proposed control system.